Study on the Optimum Flushing Volume of the Sewer System in South Tangerang City - Maudi Larasati Marsudi; T. Tazkiaturrizki; W. Winarni (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2018)
Aims: This planning aims to obtain the optimum flush volume on the design of sewerage in South Tangerang City. Methodology and results: Factors affecting this flushing are the length of pipelines, the service area, and topographic conditions. The sewer drain that needs flushing is Line 1–WWTP since the minimum velocity is not eligible due to its relatively low average topographic slope. The flushing is required particularly for the Section 1–2. Hence, two alternatives were devised by dividing the Population Equivalent (PE) in Section 1–2 into three segments. Those alternatives were differentiated by the PE—20%, 5%, and 75% for Alternative 1; whereas 10%, 15%, and 75% for Alternative 2. Alternative 1 requires flushing on Section 1–1.1 since it has a dmin of 7 cm and vmin of 0.2585 m/s, yielding a flush volume of 3.94 m3 (0.0193 m3/s). Section 1.1–1.2 still needs flushing because this channel has a vmin of 0.4281 m/s and a qualified dmin of 15 cm, generating a flush volume of 7.89 m3 (0.2113 m3/s). Flushing is not necessary for Section 1.2–2 due to its sufficient dmin of 63 cm and vmin of 0.88 m/s. Alternative 2 requires flushing on Section 1–1.1 since it has a dmin of 7 cm and a vmin of 0.2585 m/s, resulting in a flush volume of 2.63 m3 (0.0193 m3/s). Section 1.1–1.2 still requires flushing on account of its vmin of 0.3877 m/s and the yielded flush volume of 18.4 m3 (0.2625 m3/s), though its dmin of 13 cm complies with the standard. Section 1.2–2 does not need flushing as it already has a dmin of 63 cm and a vmin of 0.88 m/s. The total flush volumes for Alternative 1 and Alternative 2 are 11.83 m3 and 21.04 m3, respectively. Conclusion, significance, and impact of the study: The total flush volume for Alternative 1 is 11.83 m3, while Alternative 2 is 21.04 m3. Thus, the optimum design having the least flush volume is Alternative 1.